2016
DOI: 10.1016/j.stem.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

CD82 Is a Marker for Prospective Isolation of Human Muscle Satellite Cells and Is Linked to Muscular Dystrophies

Abstract: Summary Cell surface markers for prospective isolation of stem cells from human skeletal muscle have been difficult to identify. Such markers would be powerful tools for studying satellite cell function during homeostasis and in pathogenesis of diseases such as muscular dystrophies. In this study, we show that the tetraspanin KAI/CD82 is an excellent marker for prospectively isolating stem cells from human fetal and adult skeletal muscle. Human CD82+ muscle cells robustly engraft into a mouse model of muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(140 citation statements)
references
References 40 publications
4
121
0
Order By: Relevance
“…Therefore, we speculate that upregulation of CD9 at the transition from MuSC (SC) to progenitor cell (P1, P2) could lead to indirect inhibition of Notch signaling via ADAMs, initiating commitment and differentiation. Another tetraspannin, CD82, has been recently identified on the surface of human muscle stem and progenitor cells 42,43 . Due to its low expression range in murine muscle cells (Supplementary Fig.3b), CD82 cannot faithfully discriminate the cell populations described here (SC, P1 and P2).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that upregulation of CD9 at the transition from MuSC (SC) to progenitor cell (P1, P2) could lead to indirect inhibition of Notch signaling via ADAMs, initiating commitment and differentiation. Another tetraspannin, CD82, has been recently identified on the surface of human muscle stem and progenitor cells 42,43 . Due to its low expression range in murine muscle cells (Supplementary Fig.3b), CD82 cannot faithfully discriminate the cell populations described here (SC, P1 and P2).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated ERBB3 + NGFR + expression enriches for PAX7 + and MYF5 + cells during the first and second trimesters of human development, including at time points when other surface markers cannot distinguish fetal muscle progenitors 43 . Shifts in ERBB3 + NGFR + expression levels reliably demarcated transitions between early and late waves of human fetal myogenesis, and correlated to the establishment of primary limb myofibers or maturation of secondary fetal myofibers.…”
Section: Discussionmentioning
confidence: 82%
“…ERBB3 + NGFR + expression was also able to demarcate progenitors from more differentiated MYOD + cells; thus, expression levels of this marker combination may serve as an important tool for studying human SMPC biology. Upon searching a recent fetal dataset, we found ERBB3 is also expressed by human fetal MCAM + cells 43 . Likewise, we found these markers enrich for myogenic SMPCs from heterogeneous hPSC cultures across multiple directed differentiation protocols 10,11,13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe an effective technique for dissociation of mononuclear cells from human muscle biopsies, and purification of a highly myogenic population utilizing FACS with the cell surface markers CD56 and CD82 (see Note 1). We recently demonstrated that CD82 is an excellent myogenic marker in both human fetal and adult skeletal muscle that is also retained on activated and differentiating myogenic progenitors (Alexander et al ., 2016). This protocol also describes methods to culture these myoblasts and confirm a myogenic population by in vitro fusion assay.…”
Section: Introductionmentioning
confidence: 99%